MANAGEMENT OF INNOVATIVE DEVELOPMENT OF THE ENTERPRISE WITH THE APPLICATION OF THE TECHNOPOLIS CONCEPT - Horiacheva, K.; Zvonenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article provides a research survey in the area of innovation development and innovation process management. It offers techno-policy model of information maintenance of innovation development. А соnсеpt is given related to industrial and administrative-territorial information flows synthesis to form а common base of knowledge in the field of management and innovation development. The growing use of new knowledge in a developed system of innovation processes has become the basis for sustainable socio-economic development of countries that are entering the late industrial and post-industrial phases of development. The analysis of current trends and the role of this new sector of the world economy, conducted by the authors, gives grounds for the following conclusions: – the results of scientific and technical (innovative) activities are one of the main resources that determines the rate of economic growth of developed countries; – the role of the new sector in the distribution of spheres of influence on the international markets of tangible assets (production volume and profit from their sale) is growing; – the role of the market of innovative products in the redistribution of price policy factors between industrialized countries and countries exporting raw materials (through a system of world prices for raw materials and prices for products made using knowledge-intensive and high technology). It is fundamentally important that the effectiveness of development in modern society is achieved not only through the development of science and industry, but also by ensuring the entire innovation cycle, from the process of acquiring new knowledge, transferring it to productive sectors of the economy and ending with their use and implementation. Since the use of new knowledge is usually carried out in order to obtain economically significant competitive advantages in the final product market, all stages of the innovation cycle are under the informational, organizational and financial influence of market factors.